PENGARUH IKLAN LAYANAN MASYARAKAT SOCIAL DISTANCING OLEH KOMINFO PADA KEWASPADAAN MAHASISWA DALAM UPAYA PENCEGAHAN VIRUS COVID-19 (SURVEY PADA MAHASISWA JAKARTA SELATAN) - Gita Arivia (2021)
Currently in the world, including Indonesia, there is a COVID-19 pandemic which is caused by a Corona virus infection. This virus is very dangerous and has caused many of death. One of the ways the government has taken to stop this pandemic is by social distancing, however it is not fully complied with by the community, especially the younger generation. The young generation is the biggest contributor and also the key to stopping this pandemic, therefore socialization is needed to increase the awareness of the younger generation. Kominfo is one of the institutions that socializes the social distancing through public service advertisements. The approach used in this research is quantitative. This study aims to describe and test how much influence social distancing public service advertisements by Kominfo have on students. The population in this study were students of South Jakarta, amounting to 197.470 people. The theory used in this study is the elaboration likehood model. The advertisement appeal measured based on the attractiveness of the theme, visual attractiveness, verbal appeal, attractiveness of advertising messages based on meaningful, believable, distinctive. While alertness is measured from alertness based on indicators of anticipation, possessiveness, and selectivity. Correlation test results are known to have a strong relationship which means that audiences who watch public service advertisements by Kominfo with the title "Fight Corona: Make Important Efforts with Social Distancing" are considered appealing by students who see and also what is delivered in the advertisement is important to know in the midst of a pandemic. Coefficient of determination results test show a strong correlation or relationship between advertiment appeal and awareness. Calculation of the significance test (t test) can be concluded that Ho is rejected and Ha is accepted.